Synthesis and in silico investigation of thiazoles bearing pyrazoles derivatives as anti-inflammatory agents. (April 2016) - Kamble, Rahul D.; Meshram, Rohan J.; Hese, Shrikant V.; More, Rahul A.; Kamble, Sonali S.; Gacche, Rajesh N.; Dawane, Bhaskar S.
Graphical abstract: Highlights: Efficient one-pot synthesis of thiazole bearing pyrazole derivatives. Compound showing selective COX-II inhibition. Molecular docking is in agreement with experimental COX-II assay. Analysis of protein–ligand interaction patterns with COX-II. Abstract: Searching novel, safe and effective anti-inflammatory agents has remained an evolving research enquiry in the mainstream of inflammatory disorders. In the present investigation series of thiazoles bearing pyrazole as a possible pharmacophore were synthesized and assessed for their anti inflammatory activity using in vitro and in vivo methods. In order to decipher the possible anti-inflammatory mechanism of action of the synthesized compounds, cyclooxygenase I and II (COX-I and COX-II) inhibition assays were also carried out. The results obtained clearly focus the significance of compounds5d, 5h and5i as selective COX-II inhibitors. Moreover, compound5h was also identified as a lead molecule for inhibition of the carrageenin induced rat paw edema in animal model studies. Molecular docking results revealed significant interactions of the test compounds with the active site of COX-II, which perhaps can be explored for design and development of novel COX-II selective anti-inflammatory agents.